Inhaled prostacyclin for Eisenmenger syndrome complicated with miliary tuberculosis - Eva M. Marwali; Novik Budiwardhana; Anna U. Rahayoe (Paediatrica Indonesiana, 2011)
Eisenmenger syndrome occurs in patients with large congenital cardiac or extracardiac left-to-right shunts. Clinically, Eisenmenger syndrome is characterized by multiple organ involvement and progressive deterioration of function over time. In the advanced stages, signs and symptoms of Eisenmenger syndrome include central cyanosis, dyspnea, fatigue, hemoptysis, syncope and right-sided heart failure. Survival of patients with Eisenmenger syndrome is generally poor, but appears to be better than that of patients with idiopathic pulmonary arterial hypertension (PAH) in a comparable functional class.1